Preparation of Chitosan-Polyvinyl Alcohol Blends and Studies on Thermal and Mechanical Properties. (2016) - Abraham, Agil; Soloman, P.A.; Rejini, V.O.
Abstract: Chitosan is a biopolymer, which is an amino polysaccharide derived from the N-deacetylation of chitin. It is a natural polymer because of the presence of degradable enzyme Chitosan. Chitosan is blended with synthetic polymer PVA with formaldehyde enhances the thermal stability. Thermogravimetric analysis was conducted to measure the weight loss of the above mentioned blend systems at a heating rate 10 o Cmin -1 in nitrogen atmosphere. It is evident that formaldehyde is acting as a cross linker for Chitosan-PVA blend which have high thermal degradation or high thermal stability when compared with Chitosan-PVA-glycerol and Chitosan-PVA blends. The presence of cross linking agents like formaldehyde decreases the solubility to certain extent, and also increases the thermal stability due to the presence of aldehyde (-CHO-) group in the formaldehyde, forming cross links with amine(-NH2-) group present in the Chitosan. This reaction is based on the Schiff's base mechanism. Various compositions of Chitosan-PVA blends have been studied for its thermal and mechanical properties. The mean tensile strength and percentage elongation of Chitosan-PVA blends decreases with decrease in PVA content. But on addition of glycerol on to the blends of Chitosan-PVA, the percentage elongations increase and mean tensile strength decreases.